2020
DOI: 10.1002/rmv.2136
|View full text |Cite
|
Sign up to set email alerts
|

Current pharmacological modalities for management of novel coronavirus disease 2019 (COVID‐19) and the rationale for their utilization: A review

Abstract: Summary SARS‐CoV‐2 has caused a pandemic which is putting strain on the health‐care system and global economy. There is much pressure to develop both preventative and curative therapies for SARS‐CoV‐2 as there is no evidence to support therapies to improve outcomes in patients with SARS‐CoV‐2. Medications that inhibit certain steps of virus life cycle that are currently used to treat other illnesses such as Malaria, Ebola, HIV and Hepatitis C are being studied for use against SARS‐CoV‐2. To date, data is limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
10
0
2
Order By: Relevance
“…Lopinavir/ritonavir and chloroquine are among drugs undergoing clinical trial with the aim of repurposing them for COVID-19 treatment. 38 However, the study that identified several medications suspected in ADRs among patients with COVID-19 linked lopinavir/ritonavir and chloroquine to a high proportion of ADRs investigated. 20 This finding has implications for policy and research, especially because there has been heated scholarly and political debates surrounding the use of these repurposed medications and their analogs in managing patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Lopinavir/ritonavir and chloroquine are among drugs undergoing clinical trial with the aim of repurposing them for COVID-19 treatment. 38 However, the study that identified several medications suspected in ADRs among patients with COVID-19 linked lopinavir/ritonavir and chloroquine to a high proportion of ADRs investigated. 20 This finding has implications for policy and research, especially because there has been heated scholarly and political debates surrounding the use of these repurposed medications and their analogs in managing patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“… [46] 3 Lopinavir/Ritonavir Acts against the viral 3CL protease. HIV, SARS, MERS [47] 4 Ribavirin Guanine analog SARS, MERS [48] Inhibition RNA-dependent RNA polymerase for replicating viral genome 5 Tocilizumab Specifically binds to soluble and membrane-bound IL-6 receptors (IL-6R), thus blocking IL-6 signalling and its mediated inflammatory response Rheumatic diseases, such as rheumatoid arthritis [49] 6 Baricitinib Jak kinas inhibitor SARS [50] 7 Remdesivir In hibition RNA-dependent RNA polymerase Hepatitis B andC, Ebola, and Marburg virus, human immunodeficiency virus (HIV) [51] 8 Favipiravir A purine nucleic acid analogue that inhibits RdRp Arenavirus, Bunyavirus, Flavivirus, and Filoviruses causing hemorrhagic fever and Ebola [52] 9 Abidol Inhibiting the fusion of viral cells into the target cell membrane(inhibition S-protein- ACE2), and preventing the virus from entering the target cell Influenza, SARS [53] 10 Ruxolitinib Janus kinase inhibitor Intermediate or high-risk myelofibrosis [54] 11 Teicoplanin A lipoglycopeptide used for treatment of gram-positive b...…”
Section: Antiviral Therapy For Covid-19mentioning
confidence: 99%
“… 4 , 5 A plethora of medical and pharmacological therapies including antivirals, antibiotics, anti‐malarials, anti‐parasitic agents, non‐steroidal anti‐inflammatory drugs, corticosteroids and immunomodulators are currently being investigated in over a thousand randomised controlled trials (RCTs) across the world with an aim to generate high‐quality evidence to inform and guide clinical practice during the ongoing pandemic. 6 , 7 , 8 , 9 , 10 , 11 Various anti‐viral drug groups such as fusion inhibitors (umifenovir), protease inhibitors (lopinavir/ritonavir), neuraminidase inhibitors (oseltamivir) and nucleotide reverse transcriptase inhibitors (remdesivir and favipiravir) have been tested in multiple prospective studies since the outbreak of the pandemic. 12 , 13 Only about 9 months ago, remdesivir became the first drug to receive United States Food and Drug Administration (US‐FDA) approval for treatment of hospitalised COVID‐19 patients.…”
Section: Introductionmentioning
confidence: 99%